Governmental Learning as a Determinant of Economic Growth - Marina Gruševaja (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2010)
Systemic economic transition is a process of determined radical institutional change, a process of building new institutions required by a market economy. Nowadays, the experience of transition countries with the implementation of new institutions could be reviewed as a method of economic development that despite similar singular steps has different effects on the domestic economic performance. The process of institutional change towards a market economy is determined by political will, thus the government plays an important role in carrying out the economic reforms. Among the variety of outcomes and effects the attention is drawn especially to economic growth that diverges significantly in different post-transition countries. The paper attempts to shed light upon the problem on the basis of institutional economics, of economics of innovation and partially of political economy of growth using an evolutionary, process-oriented perspective. In this context the issue central to the promotion of economic growth is the successful implementation of new institutions through governmental activities. The paper shows that under the conditions of bounded rationality and radical uncertainty economic growth is determined, inter alia, by the capacity for governmental learning. – – Wirtschaftlicher Systemübergang ist ein Prozess des determinierten radikalen institutionellen Wandels, ein Prozess der Transformation institutioneller Rahmenbedingungen in Richtung Marktwirtschaft. Aus heutiger Perspektive kann die Erfahrung der Transformationsländer mit der umfassenden Veränderung des institutionellen Rahmens als eine Methode der wirtschaftlichen Entwicklung gewertet und analysiert werden. Trotz ähnlicher Vorgehensweise sind das institutionelle Ergebnis und seine Auswirkungen auf die Wirtschaftsleistung in den Post-Transformationsländern sehr unterschiedlich. Institutioneller Systemwandel hin zu einer Marktwirtschaft wird durch den politischen Willen bestimmt. Damit spielt die Regierung bei der Wahl und der Durchführung von institutionellen Wirtschaftsreformen eine wichtige Rolle. Ohne auf die Vielzahl von partialen Ergebnissen dieser Reformen einzugehen, untersucht das Diskussionspapier die Auswirkungen des staatlichen Handelns auf das Wirtschaftswachstum, das in verschiedenen Post-Transformationsländern sehr stark divergiert. Die zentralen Fragen sind dabei, wie der umfassende institutionelle Wandel durch die staatlichen Aktivitäten beeinflusst wird und ob und wie innovative institutionelle Lösungen zustande kommen können. Die Fragestellung wird auf der Grundlage der Institutionenökonomik, der Innovationsökonomik und der politischen Ökonomie des Wachstums angegangen und aus einer evolutionären, prozessorientierten Perspektive am Beispiel der Länder China und Russland beleuchtet. Der Diskussionsbeitrag zeigt, dass unter den Bedingungen begrenzter Rationalität und radikaler Unsicherheit das wirtschaftliche Wachstum, inter alia, von dem Ausmaß und der Realisierbarkeit von Governmental Learning bestimmt ist.
urn:nbn:de:101:1-201101142392
Keywords: B52; D80; O43; 330; Economic transition; institutional change; governmental learning; economic growth; Ökonomische Transformation; institutioneller Wandel; Governmental Learning; Wirtschaftswachstum